2001
DOI: 10.1038/sj.onc.1204755
|View full text |Cite
|
Sign up to set email alerts
|

Induction of FGF receptor 2-IIIb expression and response to its ligands in epithelial ovarian cancer

Abstract: Epithelial ovarian cancers (EOCs) arise in the Ovarian Surface Epithelium (OSE). This tissue is a simple, poorly committed mesothelium which exhibits characteristics of epithelial and mesenchymal cells when grown in culture. In contrast, EOCs frequently exhibit properties of complex epithelial tissues of the female reproductive tract, such as oviductal, endometrial and cervical epithelia, and show induction of expression of epithelial markers such as E-cadherin. Fibroblast Growth Factor Receptor 2 isoform IIIb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 34 publications
4
50
1
Order By: Relevance
“…It has been reported that FGF-1 and -2 are expressed in some human cancers and that autocrine loops for these factors could be linked to aggressive clinical behavior (Yoshimura et al, 1998;Chandler et al, 1999;Powers et al, 2000;Steele et al, 2001). These findings are consistent with constitutive FGF-1 and -2 production directly affecting cell motility, invasiveness, tumorigenicity, and tumor angiogenesis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It has been reported that FGF-1 and -2 are expressed in some human cancers and that autocrine loops for these factors could be linked to aggressive clinical behavior (Yoshimura et al, 1998;Chandler et al, 1999;Powers et al, 2000;Steele et al, 2001). These findings are consistent with constitutive FGF-1 and -2 production directly affecting cell motility, invasiveness, tumorigenicity, and tumor angiogenesis.…”
Section: Discussionsupporting
confidence: 78%
“…The multifunctional growth factors FGF-1 and -2 and their receptors may play a role in autocrine and paracrine growth control of malignant tumors; their overproduction or a constitutive activation of FGF signaling is often associated with cancer (Yoshimura et al, 1998;Chandler et al, 1999;Steele et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To test this, we examined a set of inhibitors at effective concentrations that specifically inhibit various RTKs, including general RTKs (genistein), IGF-1R (AG1024), fibroblast growth factor receptor 1 (SU5402), epidermal growth factor receptor (EGFR) (AG1478) and hepatocyte growth factor receptor c-Met (K252a), which have been previously implicated in the progression and metastasis of ovarian cancer (Ellerbroek et al, 2001;Steele et al, 2001;Brokaw et al, 2007;Sawada et al, 2007). Among these inhibitors, we found that only genistein used to block RTK or AG1024 used to inhibit IGF-1R led to a marked decrease in p120 ctn activation ( Figure 3a) and translocation ( Figure 3b) following GnRHa stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, alternative mRNA splicing leads to isoforms of FGFR that have unique ligand-binding properties (Powers et al, 2000). Taking into account our data and the detailed studies in ovarian cancer (Steele et al, 2001;Valve et al, 2000), we could focus on either FGFR2 or FGFR4 as possible candidates for FGF2 specific signaling. Owing to the reported complexity of FGFs/FGFRs expression and the relevance of the cellular context in their interaction, further studies are needed to define the relative contribution of the two receptors, and to know which isoform of FGFR2 is relevant in FGF2 signaling on normal and tumor cells.…”
Section: Discussionmentioning
confidence: 99%